The application of periodisation models for athletes of different standards - A practical approach - Abbott, C. (Journal of Australian Strength and Conditioning, 2016)
The most highly regarded sports scientists claim that programming is not an exact science, and therefore there is no absolute right answer in determining the best approach to planning and organization. However, using the underpinning principles behind periodisation, any coach should be able to adapt the experts` models to the specific needs of their athletes. The aim of this paper is to provide an insight into the successful application of periodisation models for athletes of different qualification. Coaches will find that the classical model of periodisation will not suit athletes who have surpassed the novice stage and need a higher level of programming to elicit ongoing positive results. The content presented herein does not simply look at different models in terms of their structure, but also provides useful information for how they are to be applied in the field. It also highlights the fact that the coach needs to take into account the unique characteristics of the athlete or team as well as the distinct sporting, cultural and political environment in which they operate. Finally, the paper offers practical suggestions for coaches on how to apply the various classifications of periodised models to their training programs. It is my own observation and desire to bring the best out of the athletes that have inspired me to address this topic. Much of the literature regarding this subject is rather technical, and I have attempted to present this in a simplistic and practical way.